2024
DOI: 10.1186/s12866-023-03170-8
|View full text |Cite
|
Sign up to set email alerts
|

Core microbiota drive multi-functionality of the soil microbiome in the Cinnamomum camphora coppice planting

Luyuan Sun,
Guilong Li,
Jiao Zhao
et al.

Abstract: Background Cinnamomum camphora (L.) Presl (C. camphora) is an evergreen broad-leaved tree cultivated in subtropical China. The use of C. camphora as clonal cuttings for coppice management has become popular recently. However, little is known about the relationship between soil core microbiota and ecosystem multi-functionality under tree planting. Particularly, the effects of soil core microbiota on maintaining ecosystem multi-functionality under C. camphora coppice planting remained unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Similarly, Chen et al reported that the core microorganisms identified in soil were associated with the nitrogen cycle . Several studies have demonstrated that the core microbiota plays a crucial role in maintaining the functional stability of the soil microbiota and driving soil nutrient cycling. In addition, core microbiota were prevalent in multiple ecological environments and used a wide range of ecological niches and resources to improve the productivity of soil ecological environments and plant quality. Therefore, identifying the core microbiota and screening potential nitrogen cycling microbes are key steps in the artificial construction of microbiota to improve soil nitrogen availability.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chen et al reported that the core microorganisms identified in soil were associated with the nitrogen cycle . Several studies have demonstrated that the core microbiota plays a crucial role in maintaining the functional stability of the soil microbiota and driving soil nutrient cycling. In addition, core microbiota were prevalent in multiple ecological environments and used a wide range of ecological niches and resources to improve the productivity of soil ecological environments and plant quality. Therefore, identifying the core microbiota and screening potential nitrogen cycling microbes are key steps in the artificial construction of microbiota to improve soil nitrogen availability.…”
Section: Discussionmentioning
confidence: 99%